TAYANGAN KARTUN LAGA DI TELEVISI DENGAN AGRESIVITAS SISWA DI SEKOLAH - Mada Kartika Elly; Nathania Bayu Astrella (Ilmu Psikologi Universitas Yudharta Pasuruan)
This research is to examine the relationship between action genre cartoons with student aggressivity. The subjects of this research are students of grade V and VI elementary school. Participative observation with aggressivity checklist was used to measure student aggressivity. Likert scale was used to measure the independent variable by using action cartoon scale. Pearson‘s product moment was used to analysis the results, found a high significance of correlation between action genre cartoon with student aggressivity.